KERAJAAN BONE DALAM LINTASAN SEJARAH SULAWESI SELATAN (SEBUAH PERGOLAKAN POLITIK DAN KEKUASAAN DALAM MENCARI, MENEMUKAN, MENEGAKKAN DAN MEMPERTAHANKAN NILAI-NILAI ENTITAS BUDAYA BUGIS) - Anzar Abdullah (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
This paer is aimed to describe how Bone as kingdom plays an important role in the context of political strength and power in South Sulawesi, at least during the period of 13 th century AD. Bone as a great kingdom, able to exist until well into the twentieth century. Althought the first half of the century, Bone as a political strength and practical power ends, because it has been controlled by the Dutch in 1905. The kingdom of Bone for more than four centuries appeared holding a hegemonic of power in South Sulawesi after the Bongaya Agreement in 1669. Since also, Bone is the heaviest rival of Dutch colonial to give its political influence in South Sulawesi. In analyzing the history Bone, the study was done by using historical methods through four stages; heuristic, criticism, in terpretation, and historiografhy. The results of study showed that Bone as one of the greatest kingdom in South Sulawesi has defeated the kingdom of Gowa and substituting its position as leader and holder of political hegemony in South Sulawesi and the eastern part of the archipelago post Bongaya Agreement in 1669-1905.